Formulation and Physical Evaluation of Sleeping Mask Gel Preparation of Mahogany Leaf Extract (Swietenia Mahagoni (L.) Jacq) As Antioxidant - Ratih, Hestiary; Sutarna, Titta Hartyana; Febrianti, Mia; Alatas, Fikri; Purnamasari, Nira (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2024)
Antioxidants are used to neutralize free radicals. Mahogany leaves (Swietenia mahagoni (L.) Jacq) contain flavonoid chemicals that exhibit antioxidant properties. The purpose of the study was to determine the physical characteristics and antioxidant activity of sleeping mask gel preparations with the addition of mahogany leaf extract. Mahogany leaf extract is made using the maceration process. Determination of antioxidant activity using the DPPH method. The formulation is made by varying the concentration of mahogany leaf extract into 4 formulas, F0 (bases, F1 (0.0195%, IC50), F2 (0.0975%, 5xIC50) and F3 (0.195%, 10xIC50). There were several tests used to evaluate formulas, including homogeneity, dispersion, viscosity, pH, and organoleptic (odor, color, and shape) testing. IC50 value of mahogany leaf extract was 19.48 μg / mL. Mahogany leaf extract antioxidant gel sleeping mask preparations F0, F1, F2 and F3 was evaluated such as organoleptic testing requirements, homogeneity and pH produced between 6.15-6.65 including the skin's normal pH range of 4.0-7.0 during 28-day storage. F2 exhibits the best antioxidant stability, with an inhibition value of 54.59%.